Technique of soil testing and plant analysis and their utilization for crop production in Malaysia - Sharifuddin, H.A.H.; Fauziah, I.; Zaharah, A.R. (Informa UK Limited, 1990)
Soil testing and plant analysis using standard procedures are widely used in Malaysia. Routine soil analysis Include determination of CEC, exchangeable cations, pH, organic carbon total N, acid flouride soluble P, total P and extractable cations. Other parameters carried out by some laboratories include.